Pengujian Kualitas Parameter Fisika Kimia dan Kandungan Total Fenol dari Teh Herbal Cakar Kucing (Uncaria tomentosa Wild. Ex Schult) Sebagai Minuman Fungsional - Tavita, Gusti Eva; Linda, Riza; Ashari, Asri Mulya; Apindiati, Rita Kurnia; Hartanti, Lucky (Agrisaintifika: Jurnal Ilmu-ilmu Pertanian, 2022)
The many side effects of consuming chemical-based drugs in maintaining human health have led to a tendency to return to nature. Consumption of medicinal plants in fresh or dried form has been considered to minimize side effects. This research will examine the feasibility of cat's claw (Uncaria tomentosa Wild. Ex Schult) tea as a functional drink based on physicochemical parameters and total phenol content. The physicochemical parameters tested included pH, water content, ash content and organoleptic examination of herbal teas including taste, odor and color of the brewed solution, while the total content of phenolic compounds was carried out based on the Folin–Ciocalteu method. Organoleptic examination showed a characteristic odor of the leaves, such as the smell of herbal teas in general with a bland and astringent taste, and the juice of the solution was yellowish green. The results of the physicochemical parameter test showed that the pH of the solution was 6.9, the water content was 7.7, the ash content was 8.00%, while the total phenol content measured was 68.77 mg GAE/g sample.  The physicochemical parameters measured from the testing of cat's claw herbal tea in this study met the quality requirements of dry tea according to SNI No 3836 BSN 2013